Growth performance and carcass characteristics of rabbits fed concentrate diets containing graded levels of Brassica oleracea outer leaves and Musa paradisiaca leaves - Doris Yaa Osei; Samuel Obeng Apori; Julius Kofi Hagan; David Amedorme; Raphael Ayizanga (World Rabbit Science, 2024)
Ninety-six (96) 8-wk-old “mixed breed” of New Zealand white, California white and chinchilla rabbits were used to determine the growth performance, carcass and organ percentages of rabbits fed concentrate diets containing graded levels of Brassica oleracea outer leaves and Musa paradisiaca leaves. The rabbits were assigned to two groups of 48. Those in group 1 were allotted to four dietary treatments with concentrate diets containing 0, 10, 20 and 30% inclusion levels of B. oleracea outer leaves for one week and 12-wk adaptation and testing periods, respectively, for growth performance evaluation. Similar treatment and design were adopted for group 2 rabbits using graded levels of M. paradisiaca leaves. Six rabbits were randomly selected from each treatment group for slaughter at the end of the testing period for carcass and internal organ characteristics evaluation. There were no dietary effects on the parameters of rabbits fed graded levels of B. oleracea outer leaves except for M. paradisiaca, where the control diet had the lowest feed intake and the least (P<0.05) feed conversion ratio comparable to 30% inclusion level and final body weight, which was the highest (P<0.05) for rabbits fed diets containing 10 and 20% inclusion levels of M. paradisiaca leaves. The cost of feed was highest for the control diets, and reduced with increasing inclusion levels of the leaves in the diets. None of the rabbits died during the experimental period. The findings suggest that rabbits can be fed concentrate diets containing B. oleracea outer leaves and M. paradisiaca leaves up to 30% inclusion level for good growth performance and high carcass characteristics at a lower production cost than concentrate diets, while maintaining good health.